The place we make : breaking the legacy of legalized hate - Sanderson, Sarah L. (WaterBrook, an imprint of Random House, 2023)
"The stunning true story of a Black man convicted and exiled from Oregon under the territory's Exclusion Law in 1851-and of a white woman wrestling with faith, racism, and privilege today after discovering that she's related to the pastor who stood by and watched"--